Efektivitas Digital Storytelling untuk Pengenalan Empati pada Anak Usia Dini - Febi Monica Karina; Anayanti Rahmawati; Muhammad Munif Syamsuddin (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2021)
This experimental study aimed to test the effectiveness of digital storytelling as a medium for  empathy introduction in early childhood. The samples used were 22 kindergarten children in group B in TK Indriyasana 1 and TK Indriyasana 5 Surakarta which were selected by probability sampling. The data were collected by using a questionnaire that measured teacher and parental assessments of children's empathetic behavior. Research finding showed that there was an increase in the average pretest and posttest scores for children's empathetic behavior after giving treatment of digital storytelling. The digital storytelling treatment resulted in an increase in empathic behavior as evidenced by an increase in the average posttest score compared to the pretest score. Hypothesis testing showed that digital storytelling is effective in introducing empathy to early childhood and it is accepted because it has a significance value of ≤0.05. However, the effective contribution is small due to other factors that were not tested in this study such as cognitive development, mood and feeling, situation and place. The implication is that digital storytelling helps early childhood recognize and know about empathy such as transmitting emotions, paying attention to other people's feelings, and taking prosocial actions.Keywords: Effectiveness of Digital Storytelling; Child Empathy; Early Childhood.    AbstrakPenelitian eksperimen ini bertujuan menguji efektivitas digital storytelling sebagai media pengenalan empati pada anak usia dini. Sampel yang digunakan berjumlah 22 anak TK kelompok B di TK Indriyasana 1 dan TK Indriyasana 5 Surakarta yang dipilih secara probability sampling. Data dikumpulkan menggunakan kuesioner yang mengukur penilaian guru dan orang tua terhadap perilaku empati anak. Temuan penelitian menunjukkan terjadi peningkatan rata-rata nilai pretest dan postest perilaku empati anak setelah pemberian treatment digital storytelling. Treatment digital storytelling mengakibatkan peningkatan perilaku empati yang dibuktikan dari peningkatan hasil rerata nilai postest dibandingkan dengan nilai pretest. Uji hipotesis menunjukkan digital storytelling efektif dalam pengenalan empati anak usia dini diterima karena memiliki nilai signifikansi ≤ 0,05. Akan tetapi, sumbang efektifnya berpengaruh kecil karena adanya faktor pengenalan empati anak usia dini lain yang tidak diuji dalam penelitian ini seperti perkembangan kognitif mood and feeling, situasi dan tempat. Implikasinya media digital storytelling membantu anak usia dini mengenal dan mengetahui tentang kemampuan berempati seperti penularan emosi, memperhatikan perasaan orang lain, dan melakukan tindakan prososial.Kata Kunci: Effectiveness of Digital Storytelling; Child Empathy; Early Childhood.